(untitled) (Journal of International Studies, 2020)
The Commonwealth has always had a central place in Malaya/Malaysia’s foreign policy, especially in the period immediately after independence and in the first few years of the formation of Malaysia. This was the period when Malaysia needed Commonwealth assistance most, in part, due to its requirement for external defence. Such assistance was not only relevant in the context of constructive cooperation but, more importantly, there was no other organization at that time in the region that could be of assistance to it. Whilst Britain was keen at accommodating Malaya as a member of the organisation upon independence, it were the Prime Ministers of Malaysia who played decisive roles in determining the extent of the relationship with the Commonwealth. The benefits Malaysia derived from such association were also heavily shaped by the styles and perceptions of successive Prime Ministers. Although the emergence of ASEAN, OIC, and other similar bodies in later years of which Malaysia is also a member, has gradually eroded Malaysia’s profound attachment to the Commonwealth, however, it has no intention of leaving the Commonwealth. It has continued to offer some degree of both tangible and intangible support to the organisation in which successive Malaysian Premiers have acknowledged its relevance to the country’s foreign policy as well as it being a useful platform to articulate Malaysia’s views on political and socio-economic matters concerning, not only Commonwealth countries, but also the world at large.